The security implications of quantum cryptography and quantum computing. Issue 9 (September 2020) - Cavaliere, Fabio; Mattsson, John; Smeets, Ben
Abstract : Classical cryptography relies on the assumption that nobody can solve a certain difficult mathematical problem in a realistic amount of time or rely on information theory arguments. Quantum cryptography relies instead on fundamental quantum physics laws. Using large quantum computers, one could break all classical asymmetric algorithms currently used for key distribution and digital signatures. Quantum computing seems to threaten many of the encryption systems in use today, which assume that nobody can solve a difficult mathematical problem in a realistic amount of time. Fabio Cavaliere, John Mattsson and Ben Smeets of Ericsson Research provide an overview of the technologies and protocols for Quantum key distribution (QKD) systems, discuss their security implications and examine standardisation activities for QKD networks. They also introduce quantum random number generators (QRNGs) as an important building block for both classical and quantum encryption systems, and address the security challenges posed by the advent of quantum computers.